2004
DOI: 10.1007/s00415-004-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of rapidly worsening multiple sclerosis for 36 months in patients treated with interferon beta plus cyclophosphamide followed by interferon beta

Abstract: Cyclophosphamide (CTX) is an alkylating agent related to nitrogen mustards whose anti-inflammatory and immunosuppressive effects have been utilised to treat selected cases of multiple sclerosis with a progressive and worsening course. To halt the progression of disease in patients refractory to disease modifying drugs CTX has been given, and several open-label studies have recently shown clinical benefits. In a previous study we demonstrated the effectiveness of a combination of IV monthly pulses of CTX and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Differently from our previous studies the population of patients here investigated were RR with an active form of disease, and poor responders to IFN β treatment. This sample could be more representative of RR MS population than the rapidly transitional groups previously described [29,30]. Thus the present results could suggest a therapeutic option for RR MS in the earlier stages of the disease when inflammatory activity is prominent.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Differently from our previous studies the population of patients here investigated were RR with an active form of disease, and poor responders to IFN β treatment. This sample could be more representative of RR MS population than the rapidly transitional groups previously described [29,30]. Thus the present results could suggest a therapeutic option for RR MS in the earlier stages of the disease when inflammatory activity is prominent.…”
Section: Discussionmentioning
confidence: 82%
“…In previous studies we demonstrated the effectiveness of a combination of IV monthly pulses of CTX and IFN β in patients with transitional MS, characterized by severe and frequent attacks and rapid progression of disability [29]. On the basis of the results obtained with the combination therapy on this group of patients and after the analysis of follow-up data which showed the maintenance of the benefits after 54 months [30], we decided to enlarge the combination treatment to those MS patients who did not seem to obtain any benefit from treatment with IFN β. The aim of the present study was to evaluate the efficacy and the safety of the combination treatment in a group of active RR MS patients previously treated with INF β.…”
Section: Introductionmentioning
confidence: 94%
“…Monotherapy use of Mito or Cy [15,[19][20][21][22][23][24] or either used in combination with immunomodulatory agents [25][26][27] has considerably increased over the last years. Despite the risk of dramatic adverse events, like severe acute or delayed heart failure [28] and acute myeloid leukaemia [20][21][22][23][24][25][26][27][28][29][30], Mito has become, after approval by the FDA and EMEA, a first-line rescue therapy for RRMS patients who do not respond to IMA and for rapidly deteriorating SPMS [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the risk of dramatic adverse events, like severe acute or delayed heart failure [28] and acute myeloid leukaemia [20][21][22][23][24][25][26][27][28][29][30], Mito has become, after approval by the FDA and EMEA, a first-line rescue therapy for RRMS patients who do not respond to IMA and for rapidly deteriorating SPMS [31][32][33][34]. Cy, although used in many MS Centres in Europe and the US [35], is not approved for MS and can be used in Italy only when informed consent is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Studies generally show that the onset of MRI effect is within 1-5 months [21]. Cyclophosphamide has also been used successfully in combination with IFN [22][23][24]. Despite different dosing schedules trials with cyclophosphamide have been consistent in showing that patients respond best if they are younger, have a shorter disease duration, and still have relapses or evidence of recent MRI activity [25,26].…”
Section: Clinical Effects and Usementioning
confidence: 99%